2022
DOI: 10.18051/jbiomedkes.2022.v5.214-220
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Asupan Kalsium dengan Intensitas Dismenore Primer pada Remaja

Abstract: Latar BelakangDismenore primer adalah nyeri perut bawah saat haid yang tidak berhubungan dengan penyakit tertentu, sebagian besar dialami oleh remaja di seluruh dunia termasuk Indonesia. Asupan kalsium dinilai berpengaruh terhadap penurunan intensitas dismenore. Kadar kalsium yang kurang dapat menyebabkan spasme dan kontraksi otot. Rerata asupan kalsium per hari pada remaja di Indonesia masih di bawah angka kecukupan kalsium yang dianjurkan. Tujuan penelitian ini adalah menilai hubungan antara asupan kalsium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Anemia can cause disturbances or obstacles to the growth of body cells and cause a lack of body resistance to pain; it can cause menstrual pain. [30] The ages of female students in this study ranged from 18-23 years old, with 120 female students at most aged 20 years. According to higher education statistics released by PDDikti, the age range of diploma 1-diploma 4 and strata 1 students in Indonesia is 19-23 years.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Anemia can cause disturbances or obstacles to the growth of body cells and cause a lack of body resistance to pain; it can cause menstrual pain. [30] The ages of female students in this study ranged from 18-23 years old, with 120 female students at most aged 20 years. According to higher education statistics released by PDDikti, the age range of diploma 1-diploma 4 and strata 1 students in Indonesia is 19-23 years.…”
Section: Resultsmentioning
confidence: 98%
“…[1] Whereas in women with a thin BMI, it can be found that there is a decrease in the body's resistance to pain due to inadequate intake of nutrients. [1] According to research by Hidayatih et al [30] intake of nutrients that affect dysmenorrhea is iron and calcium. If there is a lack of calcium, the muscles can experience cramps; as a result, the muscles cannot relax after contractions.…”
Section: Resultsmentioning
confidence: 99%
“…The consumption of calcium or magnesium supplements reduces dysmenorrhea complaints and premenstrual syndrome symptoms in women aged 19-23 years. However, not all research results prove a relationship between the level of magnesium consumption and dysmenorrhea, some research results say that there is no relationship between them (Carolina & Devita, 2022).…”
Section: The Effect Of Magnesium (Mg) On Primary Dysmenorrheamentioning
confidence: 96%